1997
DOI: 10.1037/0022-3514.72.6.1297
|View full text |Cite
|
Sign up to set email alerts
|

Who's the boss? Differential accessibility of dominance ideation in parent–child relationships.

Abstract: The accessibility of dominance ideation (as opposed to other types of ideation) was measured among parents with high or low perceived power as caregivers. Parents made comparative judgments of self versus child under concurrent memory load or no-load conditions. As predicted, dominance comparisons were found to be highly accessible for low-power parents; that is, attentional load served to increase response latencies in all conditions except those in which low-power parents made dominance judgments. Under cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 58 publications
0
42
0
Order By: Relevance
“…Using a variety of intriguing experimental paradigms, including assessments of mothers' attributions and behavior in interactions with their own and other children and with computer-simulated children, Bugental and colleagues (e.g., Bugental, Blue, & Cruzcosa, 1989;Bugental, Lyon, Krantz, & Cortez, 1997) have demonstrated that mothers who have a low sense of perceived control in care giving interactions (and attribute high control to the child) respond to challenging child behavior with more coercive parenting. Maternal depressed mood also has been found to increase the negativity of attributions for child behavior (e.g., Geller & Johnston, 1995a;White & Barrowclough, 1998).…”
Section: Moderators Of the Relations Among Child Behaviors Parental mentioning
confidence: 98%
“…Using a variety of intriguing experimental paradigms, including assessments of mothers' attributions and behavior in interactions with their own and other children and with computer-simulated children, Bugental and colleagues (e.g., Bugental, Blue, & Cruzcosa, 1989;Bugental, Lyon, Krantz, & Cortez, 1997) have demonstrated that mothers who have a low sense of perceived control in care giving interactions (and attribute high control to the child) respond to challenging child behavior with more coercive parenting. Maternal depressed mood also has been found to increase the negativity of attributions for child behavior (e.g., Geller & Johnston, 1995a;White & Barrowclough, 1998).…”
Section: Moderators Of the Relations Among Child Behaviors Parental mentioning
confidence: 98%
“…Although power plays a pivotal role in many aspects of life, from the workplace (1) to the family (8) to romantic relationships (9), little is known empirically about the course of power in everyday life. Without such data, it is unclear how power is experienced by individuals on a daily basis, including basic facts such as whether having or lacking power is a regular or rare occurrence and to what degree individuals fluctuate in their level of power throughout the day.…”
mentioning
confidence: 99%
“…Because the effects of power are known to change when power involves meaningful interpersonal interactions versus hypothetical scenarios or anticipated interactions (14), and when power differences are experienced as appropriate and legitimate versus arbitrarily assigned (15,16), it is not a given that theories developed in the experimental laboratory will generalize to real-world power experiences. Furthermore, if power operates in aspects of life beyond work, it is important to determine if theories of power (3,4) hold true across all these contexts, such as family relationships involving more complicated power dynamics (8).…”
mentioning
confidence: 99%
“…As Bugental (Bugental, Krantz, Lyon, & Cortez, 1997) showed in her research, parental aggressive behaviors towards the child are caused by the parent's lack of feeling that he/she can control what is happening in his/her interactions with the child. When children experience aggressive behaviors they may withdraw from their relationship with the parent (Bugental & Happaney, 2000).…”
Section: Discussionmentioning
confidence: 99%